Single exposure to cocaine impairs aspartate uptake in the pre-frontal cortex via dopamine D1-receptor dependent mechanisms. (4th August 2016) - Sathler, Matheus Figueiredo; Stutz, Bernardo; Martins, Robertta Silva; dos Santos Pereira, Maurício; Pecinalli, Ney Roner; Santos, Luis E.; Taveira-da-Silva, Rosilane; Lowe, Jennifer; de Freitas, Isis Grigorio; de Melo Reis, Ricardo Augusto; Manhães, Alex C.; Kubrusly, Regina C.C.
Highlights: Cocaine decreases [ 3 H]-d -aspartate uptake in P15 mice cerebral cortex. Cocaine increases phosphorylation of serine residues on EAATs, without altering their expression levels. Regulation of the EAATs by cocaine is mediated by the D1 receptor-cAMP-PKA pathway. Cocaine increasesd -aspartate, l -glutamate andd -serine extracellular levels. Abstract: Dopamine and glutamate play critical roles in the reinforcing effects of cocaine. We demonstrated that a single intraperitoneal administration of cocaine induces a significant decrease in [ 3 H]-d -aspartate uptake in the pre-frontal cortex (PFC). This decrease is associated with elevated dopamine levels, and requires dopamine D1-receptor signaling (D1R) and adenylyl cyclase activation. The effect was observed within 10 min of cocaine administration and lasted for up to 30 min. This rapid response is related to D1R-mediated cAMP-mediated activation of PKA and phosphorylation of the excitatory amino acid transporters EAAT1, EAAT2 and EAAT3. We also demonstrated that cocaine exposure increases extracellulard -aspartate, l -glutamate andd -serine in the PFC. Our data suggest that cocaine activates dopamine D1 receptor signaling and PKA pathway to regulate EAATs function and extracellular EAA level in the PFC.